Anti-Tumor Effects of Engineered VNP20009-Abvec-Igκ-mPD-1 Strain in Melanoma Mice via Combining the Oncolytic Therapy and Immunotherapy - De-Xi Zhou; Xiao-He Wang; Xuan Xu; Wen-Jie Chen; Jing Wei; Ting-Tao Chen; Hong Wei (MDPI AG, 2022)
Programmed cell death protein 1/Programmed cell death ligand 1 (PD-1/PD-L1) immune checkpoint inhibitors are the most promising treatments for malignant tumors currently, but the low response rate limits their further clinical utilization. To address this problem, our group constructed an engineered strain of VNP20009-Abvec-Igκ-mPD-1 [V-A-mPD-1 (mPD-1, murine PD-1)] to combine oncolytic bacterial therapy with immunotherapy. Further, we evaluated its growth performance and mPD-1 expression ability in vitro while establishing the melanoma mice model to explore its potential anti-cancer effects in tumor therapy. Our results indicated that the V-A-mPD-1 strain has superior growth performance and can invade B16F10 melanoma cells and express PD-1. In addition, in the melanoma mice model, we observed a marked reduction in tumor volume and the formation of a larger necrotic area. V-A-mPD-1 administration resulted in a high expression of mPD-1 at the tumor site, inhibiting tumor cell proliferation via the down-regulation of the expression of rat sarcoma (Ras), phosphorylated mitogen-activated protein kinase (p-MEK)/MEK, and phosphorylated extracellular signal-regulated kinase (p-ERK)/ERK expression significantly inhibited tumor cell proliferation. Tumor cell apoptosis was promoted by down-regulating phosphoinositide 3 kinase (PI3K) and protein kinase B (AKT) signaling pathways, as evidenced by an increased Bcl-2-associated X protein/B cell lymphoma-2 (Bax/Bcl-2) expression ratio. Meanwhile, the expression levels of systemic inflammatory cytokines, such as interleukin-6 (IL-6), interleukin-1β (IL-1β), and tumor necrosis factor-α (TNF-α), were substantially reduced. In conclusion, our research demonstrated that V-A-mPD-1 has an excellent anti-tumor effect, prompting that the combined application of microbial therapy and immunotherapy is a feasible cancer treatment strategy.